Dilemma of and China’s Response to the Application of the Rules on Investors’ Reasonable Expectations from the Perspective of International Investment Arbitration - Xu, Guangzhao (Transactions on Economics, Business and Management Research, 2024)
The rule on investors’ reasonable expectation aims to protect the rights and interests of foreign investors, which is often cited by arbitral tribunals in the practice of international investment arbitration in recent years. It can be divided into different categories according to its different bases. However, there are many problems in the application of this principle in the practice of international investment arbitration. Based on its significance in protecting the legitimate rights and interests of investors as well as the universality of the use of arbitral tribunals, the improvement of relevant clauses and due diligence and specific written commitments are the focus of countries and investors. It is also necessary for all host countries and investors to properly handle and break through this dilemma. If China is the host country, relevant applicable risk plans should be given to implement the national strategy of “going global” for Chinese enterprises.